Perioperative Outcomes of Intramedullary Nail vs Hemiarthroplasty vs Total Hip Arthroplasty for Intertrochanteric Fracture: An Analysis of 31,519 Cases - Natalia Czerwonka, MD; Sohil S. Desai, MD; Puneet Gupta, MD; Roshan P. Shah, MD, JD; Jeffrey A. Geller, MD; H. John Cooper, MD; Alexander L. Neuwirth, MD (Arthroplasty Today)
Background: The purpose of this study is to compare 30-day perioperative outcomes following treatment of intertrochanteric (IT) fractures with intramedullary nail (IMN), total hip arthroplasty (THA), or hemiarthroplasty (HA). Methods: Using the National Surgical Quality Improvement Program database, we conducted a retrospective cohort study of patients who had sustained an IT fracture treated with primary IMN, THA, or HA between 2017 and 2020. International Classification of Diseases, 10th Revision codes S72.141-S72.146, subtypes A through C, were used to identify eligible patients and were cross-referenced to primary Current Procedural Terminology codes, used to identify the following procedure types: 27245: IMN; 27130: THA; and 27236: HA. Revision cases and patients who underwent arthroplasty for osteoarthritis were excluded. Outcomes of interest included reoperation, readmission, operative time, length of stay, and major and minor complications. Multivariate regression was used to evaluate differences in postoperative outcomes between groups. Results: There were 29,809 IT fractures treated with IMN (94.6%), 1493 treated with HA (4.7%), and 217 treated with THA (0.70%). There was a statistically significant increase in 30-day reoperation rates (adjusted odds ratio [aOR] = 1.99 [95% confidence interval = 1.51, 2.63], P < .001) when combining all arthroplasty patients compared to IMN. There was no statistically significant difference in the overall complication rate between IMN (13.58%) and HA (14.60%, aOR = 1.09, P = .315) or THA (11.98%, aOR = 1.00, P = .998). When compared to IMN (0.12%), there was a statistically significantly decreased need for transfusion in the HA group (aOR = 0.71 [95% confidence interval = 0.61, 0.80], P < .001). Conclusions: Primary HA is associated with an increased 30-day reoperation rate and decreased need for blood transfusion, but there were no other significant differences in postoperative morbidity identified among IMN, THA, and HA in the treatment of IT fractures. Given the challenges and inferior outcomes associated with conversion arthroplasty, the lack of significant difference in morbidity between the 3 groups suggests that primary arthroplasty may be a safe and viable treatment option in selected patients with IT fractures. Comparative studies with longer clinical follow-up will be necessary to establish the appropriate indications and further evaluate the clinical outcomes of primary arthroplasty in the treatment of IT fractures.